Are we closer to having drugs to treat muscle wasting disease?. Issue 2 (28th May 2014) - Morley, John E.; von Haehling, Stephan; Anker, Stefan D.
Abstract : The two most common muscle wasting diseases in adults are sarcopenia and cachexia. Despite differences in their pathophysiology, it is believed that both conditions are likely to respond to drugs that increase muscle mass and muscle strength. The current gold standard in this regard is exercise training. This article provides an overview of candidate drugs to treat muscle wasting disease that are available or in development. Drugs highlighted here include ghrelin agonists, selective androgen receptor molecules, megestrol acetate, activin receptor antagonists, espindolol, and fast skeletal muscle troponin inhibitors.